IS IT A BUSINESS FEEDING ON EMOTIONS OR AN ACT OF ALTRUISM? THE CASE OF FINANCING FOOTBALL IN POLAND - Majewski, Sebastian Mariusz (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The main goal of this article is to verify the hypothesis on the behavioural character of the relationships between enterprises financing football in Poland and the fans of this sport. In his research, the author analyses selected companies listed on the Warsaw Stock Exchange which are engaged in financing football in the Polish Ekstraklasa. The author uses the quotations of such companies as: Ruch Chorzow, Comarch, KGHM, Tauron, Lotos and Police. It is possible to divide these companies into three groups: owners (Comarch, KGHM), sponsors (Tauron, Lotos, Police) and one public company (Ruch). In the research, ARCH models are used based on econometric models with independent variables: sporting results and betting odds.